Nilai-Nilai Patriotisme Pada Lirik Lagu Los! Los! Los! Karya Hotaru Kajian Semiotika Riffaterre - Hastuti, Nur; Fakhliza, Shaila (Vocational College of Diponegoro University, 2025)
This article analyzes the value of patriotism in the lyrics of the opening song of a Japanese animation titled